NF-κB inhibition attenuates LPS-induced TLR4 activation in monocyte cells - Wan, Jian (Mol Med Rep, 2016)
Toll-like receptor (TLR) family are receptors for extracellular or intracellular signaling, such as lipopolysaccharide (LPS), or 12-O-tetradecanoylphorbol-13-acetate. TLR induces the differentiation of human myeloid monocytic-leukemia cells (THP-1) to macrophages. However, the relationship between extracellular or intracellular signaling and the TLR protein level remain to be determined. Using RT-PCR and western blot analysis, the aim of the present study was to determine whether TLR4, a major TLR family member, could be moderately upregulated by high concentration of LPS and whether it promoted the maturation of THP1 cells. The results showed that, upregulated TLR4 at the protein level and mRNA level enriched the TLR4 modulation style. In addition, TLR4 expression was blocked by nuclear factor (NF)-κB inhibitor, and LPS stimulated NF-κB binding in the TLR4 gene promoter. Therefore, the increased expression of TLR4 in the responsiveness of LPS-treated THP1 cells occurred in response to the upregulation of their respective receptors, as well as a tight binding of NF-κB in the TLR4 gene promoter.